Me or others? Hard Luxury Purchase Intention during the COVID-19 Pandemic - Phang Ing @ Grace; Zaiton Osman; Izyanti Awang Razli (Sarawak Research Society, 2021)
The recent outbreak of COVID-19 has changed the world drastically. Consumers are predicted to think, react and behave differently during and after the pandemic. This study is carried out to examine consumers’ purchase intention of luxury brands, by comparing the influences of perceived values (e.g. experiential, functional and symbolic) and social influence. A total of 200 valid responses were collected via purposive sampling technique and the framework was tested using structural equation modeling. The findings indicated significant roles of experiential, functional and symbolic value perceptions in forming of luxury purchase intention, compared to the influence of social groups during the time of pandemic. The findings provide valuable insights for marketing practitioners to plan for effective positioning and marketing mix strategies; and for academicians to have better understanding of the consumers’ cognitive and conative structures during the time of COVID-19 pandemic.